The challenges of anti-doping education implementation in Kenya: Perspectives from athletes and anti-doping educators - Juma, B. O.; Woolf, J.; Bloodworth, A. (Performance Enhancement & Health, 2022)
Background: Kenyan athletes are at a significantly higher risk of doping, with research suggesting that their anti-doping knowledge is poor. WADA actively promotes education to prevent doping however, these efforts should account for regional contexts. The purpose of this study was to understand the challenges of anti-doping education by examining the experience that Kenyan athletes and educators have had with these programs. Methods: Semi-structured interviews were conducted with eleven long-distance runners and two anti-doping educators. Athletes and educators were included to understand the experience of delivering and receiving anti-doping education. Thematic analysis was performed on the data. Results: Three main themes were identified. First, the athletes questioned the quality of education and expressed skepticism about its effectiveness. Furthermore, issues of accessibility surfaced with elite athletes receiving priority. Second, in the absence of education, athletes relied upon coaches and managers as information sources, which opened avenues for athlete exploitation. Third, athletes perceived doping as prevalent and easy to engage in. Moreover, some athletes believed that the Anti-Doping Agency of Kenya and the Athletics Federation were colluding to protect some athletes and this perception challenged the legitimacy of these organizations. Conclusions: While efforts to deliver anti-doping education in Kenya have improved, sub-elite and developing athletes may be neglected. This leads to an overreliance on informal sources of information and the potential for athlete exploitation. In developing countries, anti-doping organizations may need to leverage the existing infrastructure of coaches to promote anti-doping education information delivery.